Analysis of cyberspace security based on game theory - Jian-ming ZHU; Qin WANG (网络与信息安全学报)
Information security economics is an important research area and game theory is one of the main basic theories and tools of cyberspace security.Based on game theory,the main problems of cyberspace securing were analyzed which including network attack and defense,cryptographic protocol design,and security technology con-figuration.The conflicts between attackers and defenders as well as the dependence among defenders were mainly analyzed on network and defense.Game theory’s applications in secret sharing and secure multi-party computation were emphasized on cryptographic protocol design.The game theory’s applications in intrusion detection system and firewall technology were analyzed on security technology configuration.Finally,the limitations of current re-searches and carries on the forecast to the future research directions were pointed out.